If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39x + 33 = 540 Reorder the terms: 33 + 39x = 540 Solving 33 + 39x = 540 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + 39x = 540 + -33 Combine like terms: 33 + -33 = 0 0 + 39x = 540 + -33 39x = 540 + -33 Combine like terms: 540 + -33 = 507 39x = 507 Divide each side by '39'. x = 13 Simplifying x = 13
| 3(x-20)=102 | | n+(n-1)=35 | | (x+1)(1+1)=9x+6 | | ln(x^2-1)=ln(x-1)+1 | | y=-4*3+15 | | y=-4*2+15 | | 2x-4(x+3)=15 | | .3x+.5y=4 | | y=-2*6+19 | | y=-2*5+19 | | 23=8x-15+3x | | -5+(-7.1)= | | 2r-(5r-r)=13 | | 2cosx-5secx=3 | | 3x+7-2x=4x+13 | | 3x+11+10x=180 | | 15(x-5)=105 | | 2a-(-18)=18 | | 4(x-15)=168 | | 2x+10+3x+10=90 | | 49x^3-xy^2= | | (x-4)2+(y+5)2=25 | | X-2/5=-4 | | 81-4y^2= | | 6x-11=-5x+6.6 | | 8h-19=15 | | 6x+13+4x-3=180 | | -7.3x=-12.4-1.1x | | 4(4x+3)+7(x-3)= | | 6s+40=184 | | 3(2x-5)/2=8 | | 4y=72^1/5 |